2020
DOI: 10.1002/advs.201902862
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Signatures Can Discriminate Unipolar from Bipolar Depression

Abstract: Discriminating depressive episodes of bipolar disorder (BD) from major depressive disorder (MDD) is a major clinical challenge. Recently, gut microbiome alterations are implicated in these two mood disorders; however, little is known about the shared and distinct microbial characteristics in MDD versus BD. Here, using 16S ribosomal RNA (rRNA) gene sequencing, the microbial compositions of 165 subjects with MDD are compared with 217 BD, and 217 healthy controls (HCs). It is found that the microbial compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 45 publications
6
124
0
Order By: Relevance
“…We modified the default calculation by controlling the multiple testing using Benjamini–Hochberg (BH) false discovery rate (FDR) correction procedure. LEfSe analysis was conducted under the following conditions: p < 0.05, FDR < 0.1 and LDA > 2.5 ( Erawijantari et al, 2020 ; Zheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We modified the default calculation by controlling the multiple testing using Benjamini–Hochberg (BH) false discovery rate (FDR) correction procedure. LEfSe analysis was conducted under the following conditions: p < 0.05, FDR < 0.1 and LDA > 2.5 ( Erawijantari et al, 2020 ; Zheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We modified the default calculation by controlling the multiple testing using Benjamini-Hochberg (BH) false discovery rate (FDR) correction procedure. LEfSe analysis was conducted under the following conditions: p < 0.05, 1 http://qiime.org/ 2 http://drive5.com/usearch/manual/uchime_algo.html 3 http://drive5.com/uparse/ 4 http://huttenhower.sph.harvard.edu/galaxy/ FDR < 0.1 and LDA > 2.5 (Erawijantari et al, 2020;Zheng et al, 2020).…”
Section: S Rrna Gene Sequence Analysismentioning
confidence: 99%
“…Relative abundance of microbial compositions was different at the phylum and family levels between MDD and BD patients. Moreover, a microbial operational taxonomic unit (OTU) panel was identified that could efficiently distinguish between bipolar and unipolar depression 43 . These two studies provided preliminary evidence on biological disparities between MDD and BD, as reflected by a different microbiome in the human intestine.…”
Section: Gut Microbiome and Bd In Human Studiesmentioning
confidence: 99%
“…This might be illustrated by the involvement of candidate hub genes underlying the pathogenesis of early death in HD, particularly CA10, which indirectly interacted with GABRB3 in the pathway of GABAergic synaptic transmission [29,34,38,41]. Five genes (CA10, WSB2, ACTR3B, PCDH19 and GABRB3) with non-zero regression coe cients were selected to conduct the ROC analysis, of which the AUC values were all greater than 70%, supporting that they were hub genes and could be served as potential predictors for early death in HD worthy of clinical application [43]. In addition, the veri cation of the Kaplan-Meier survival curve demonstrated that, compared with the high expression of CA10, WSB2, ACTR3B, PCDH19 and GABRB3, their low expression was associated with shorter overall survival of HD patients.…”
Section: Discussionmentioning
confidence: 84%